Microscopic distribution of alkaloids in freeze-fixed stems of Phellodendron amurense - Gong, Qinyue; Aoki, Dan; Matsushita, Yasuyuki; Yoshida, Masato; Taniguchi, Toru; Endoh, Keita; Fukushima, Kazuhiko (Frontiers in Plant Science, 2023)
Phellodendron amurense Rupr. contains rich alkaloids, which have been extensively applied in clinical treatments for their various biological activities. However, detailed microscopic distribution and roles of such alkaloids in P. amurense stem still need to be clarified. In this study, the distribution of eight alkaloids in the transverse surface of freeze-fixed P. amurense stems in fall and summer has been visualized by cryo-time-of-flight secondary ion mass spectrometry and scanning electron microscopy (cryo-TOF-SIMS/SEM), which was found in living tissues with relative contents of different alkaloids varying with the position. In addition, the contents of these alkaloids quantified by high-performance liquid chromatography (HPLC) analysis suggested the seasonal variation from fall to the following summer. Results obtained were discussed with the possible in planta role of alkaloids.